Early Onset of Periodic Fever Syndrome in a Patient Carrying Both Tumor Necrosis Factor Receptor Superfamily 1A and Mediterranean Fever Mutations - Barbara KRASZEWSKA-GŁOMBA,; Zofia SZYMAŃSKA-TOCZEK,; Leszek SZENBORN, (Archives of Rheumatology, 2016)
In this article, we report a nine-month-old male patient with a history of three unexplained, prolonged attacks of high fever, including one in the neonatal period, accompanied by an erythematosus, migratory rash. There was no family history that might have suggested a hereditary periodic fever syndrome, but the overall clinical picture was in accordance with tumor necrosis factor receptor-associated disease. Genetic analysis revealed two heterozygous mutations: C30Y in the tumor necrosis factor receptor superfamily 1A gene and K695R in the Mediterranean fever gene. This case shows that diagnosis of an autoinflammatory syndrome should be considered even in the youngest infants with incomplete presentation and no family history of recurrent fever.